2014
DOI: 10.1109/tcst.2013.2293954
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of a Network of Power Microgrids Using the Pontryagin's Minimum Principle

Abstract: The optimal control of the power flows in a network\ud of microgrids (MGs) is presented. The problem is solved using\ud the mathematical formalization of the optimal control based on\ud the Pontryagin’s minimum principle (PMP). The objective is to\ud deliver an optimal control strategy for the minimization of the\ud power flows among MGs, and to maintain the storage system\ud operating around a given reference value. This study proposes\ud an original formulation based on the PMP that may be viewed as\ud a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…The main drawback of the approach is again related to unbounded character of the state and control variables resulting from the optimization problem. Dagdougui et al [16] solved a similar problem using an original modeling approach based on the mathematical formalization of the Pontryagin minimum principle. Despite the inclusion of the constraints, the approach remains more on the theoretical side as it is difficult to implement it for real cases.…”
Section: Introductionmentioning
confidence: 99%
“…The main drawback of the approach is again related to unbounded character of the state and control variables resulting from the optimization problem. Dagdougui et al [16] solved a similar problem using an original modeling approach based on the mathematical formalization of the Pontryagin minimum principle. Despite the inclusion of the constraints, the approach remains more on the theoretical side as it is difficult to implement it for real cases.…”
Section: Introductionmentioning
confidence: 99%
“…From this table, it is seen that alternatives A 1 and A 3 are selected by the aggregators. Hence, a risk matrix is defined for these alternatives from (18) and (19), as given in Table XII. From this table, alternative A 3 (i.e., {MG-1, MG-2}) is selected as it demonstrates a lower risk index.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The trade of power among MGs in the system of CMGs is addressed in [18]. Optimal control of a distribution network composed of utility-connected MGs forming a CMG is also studied in [19]. Dynamic operation of DERs within CMGs is investigated in [20] and the dynamic security of the CMGs is examined in [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since all DERs have the same f , from (2) it can be concluded that (15) is satisfied if the UAPC of each DER of MG-1 is less than α 2 times of the maximum capacity of that DER, that is…”
Section: B Proposed Decentralized Approachmentioning
confidence: 99%
“…The trade of power among MGs in CMG is addressed in [13] and [14]. Optimal control of a distribution network composed of utility-connected MGs forming a CMG is studied in [15]. The dynamic operation of DERs within CMGs is investigated in [16] and the dynamic security of the CMGs is examined in [17].…”
Section: Introductionmentioning
confidence: 99%